Automedicación en los alumnos del X ciclo de la Facultad de Farmacia y Bioquímica de la Universidad Nacional de Trujillo – 2009” - Azañero Pablo, Marcos David (2011)
This descriptive research, conducted at the Faculty of Pharmacy and Biochemistry, National University of Trujillo - 2009, was aimed at determining the incidence of student self-medication in this population. The sample was a comprised of 122 students from X cycle were surveyed manually process information from a spreadsheet in Microsoft Office Excel 2007. The results show that self-medication occurs in both sexes. Regarding gender, the female was the one who made greater use of medications by self-medication in this faculty (53.28%), but required the drug groups were the NSAIDs followed by antibiotics, while the main reason given for drug use in this faculty is the breathing problem (27.69%), the source of information used for this practice were the books of pharmacology because of their knowledge of this population, and pharmacy is the greatest source of acquisition